Analysis Of Taxpayer Knowledge And Awareness Of Compliance To Pay Motor Vehicle Tax Mediated By Tax Whitening Policy - Vita Adi Meli Yana; Bayu Kurniawan; Rita Meiriyanti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine the Analysis of Knowledge and Awareness of Taxpayers on Compliance to Pay Motor Vehicle Tax Mediated by Tax Bleaching Policy (Case Study at Samsat Kota Semarang) The population used in the study was WP PKB which was recorded at SAMSAT Semarang City and the sample used was 385 SAMSAT Motor Vehicles Semarang City using purposive sampling. Data analysis in the study using Smart PLS software version 4.0. The R-Square value of the Tax Bleaching Policy variable is (0.869), this proves that the strength of the tax knowledge variable and taxpayer awareness can be explained through the Tax Bleaching Policy variable of 86.9% (moderate category). The R-Square value of the Taxpayer Compliance variable is (0.755), this shows that the strength of the tax knowledge variable and taxpayer awareness together with the Tax Bleaching Policy can be explained through the Taxpayer Compliance variable of 75.5% (moderate category).